2019
DOI: 10.1186/s13104-019-4855-2
|View full text |Cite
|
Sign up to set email alerts
|

Gulf War Illness-associated increases in blood levels of interleukin 6 and C-reactive protein: biomarker evidence of inflammation

Abstract: ObjectiveGulf War Illness is a chronic multisymptom disorder severely impacting the health and well-being of many Veterans of the 1990–1991 Gulf War. Symptoms that define the disease include pain, fatigue, mood and memory impairments, gastrointestinal problems, lung disorders, and skin rashes. In our previous biomarker study, we discovered Gulf War Illness-associated proinflammatory blood biomarkers. Therefore, we hypothesized that chronic inflammation causes the symptoms that define this disorder. Testing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
2
37
2
Order By: Relevance
“…Neuroimaging has been found to be useful as a differential diagnostic tool for GW ill versus GW healthy individuals; however, what has been missing is the ability to use a less invasive, more readily available, and less costly tool, such as blood biomarkers to differentiate GWI from GW healthy status and differentiate GWI from another chronic multisymptom discord [ 6 , 8 ]. There have been some encouraging blood biomarker studies reporting differences between GWI cases and controls on neuroinflammatory markers that require validation in other GWI cohorts [ 9 , 10 , 11 ]. In addition, recently, we reported on a pilot study of serum biomarkers, which found seven out of eight markers significantly differed in veterans with GWI versus symptomatic controls with lower back pain, suggesting new potential blood markers for GWI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging has been found to be useful as a differential diagnostic tool for GW ill versus GW healthy individuals; however, what has been missing is the ability to use a less invasive, more readily available, and less costly tool, such as blood biomarkers to differentiate GWI from GW healthy status and differentiate GWI from another chronic multisymptom discord [ 6 , 8 ]. There have been some encouraging blood biomarker studies reporting differences between GWI cases and controls on neuroinflammatory markers that require validation in other GWI cohorts [ 9 , 10 , 11 ]. In addition, recently, we reported on a pilot study of serum biomarkers, which found seven out of eight markers significantly differed in veterans with GWI versus symptomatic controls with lower back pain, suggesting new potential blood markers for GWI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…GWI animal models have validated the involvement of neuroinflammatory mechanisms in the pathology of the disease ( 10 ), including the over-reactivity of astrocytes and microglia. This increased activation of immune cells was also directly observed in the brain of veterans with GWI ( 11 ), while inflammatory biomarkers such as elevated levels of pro-inflammatory cytokines, IL-1β, INF-γ, or IL-6 ( 12 , 13 ) have been found in the serum of GWI patients. Increased concentrations of inflammatory cytokines are also associated with different mood disorders, including bipolar and major depressive disorders ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 74%
“…inflammatory biomarkers such as elevated levels of proinflammatory cytokines, IL-1b, INF-g, or IL-6 (12,13) have been found in the serum of GWI patients. Increased concentrations of inflammatory cytokines are also associated with different mood disorders, including bipolar and major depressive disorders (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…As previous reports, excessive neuroin ammation presented in veterans suffering from GWI and also observed in animal model of GWI 21,41 . Part of serum proteins associated with in ammation were signi cantly increased in veterans suffering from GWI, including interleukin 6, C-reactive protein, matrix metalloproteinase-9 (MMP-9) and matrix metalloproteinase-2 (MMP-2) 42,43 . In animal model of GWI, suppression of the in ammatory responses showed a neuroprotective effect, improved neurogenesis, and better cognitive and mood function 44 .…”
Section: Discussionmentioning
confidence: 99%